2014
DOI: 10.11646/zootaxa.3841.4.1
|View full text |Cite
|
Sign up to set email alerts
|

On some Palaearctic click beetles deposited in the Hungarian Natural History Museum, 2 (Coleoptera: Elateridae)*

Abstract: One new genus (Roznerathous gen. n.) and 31 new species of Elateridae are described: Athous szalokii sp. n. (Georgia), Agriotes balikesirensis sp. n. (Turkey), Agriotes rozneri sp. n. (Syria), Agriotes sakaryaensis sp. n. (Turkey), Cardiophorus anatolicus sp. n. (Turkey), Cardiophorus aranyos sp. n. (Afghanistan), Cardiophorus burkus sp. n. (Afghanistan), Cardiophorus dicronychoides sp. n. (Afghanistan), Cardiophorus podlussanyi sp. n. (Turkey), Cardiophorus tenuis sp. n. (Armenia), Coptostethus attilai sp. n.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…All available illustrations of Coptostethus species were examined (Cobos , , ; Németh & Platia ; Platia , ; Platia & Kakiopoulos ) to identify variability in diagnostic characters in the bursa copulatrix sclerites. The following species had proximal sclerites moderate to broad (Figs 21,24), nearly symmetrical with a median groove and narrow (petiolate) base; distal sclerites fused and weakly sclerotized, and base of spermathecal gland duct surrounded by sclerotized ring: Coptostethus buci Németh & Platia, ; C. salvatoi Platia in Platia & Kakiopoulos, ; C. oromii (Cobos, ); C. machadoi (Cobos, ); C. vittatus (Lindberg, 1953); C. crassiusculus Wollaston, 1864; C. vestitus Lindberg, 1953; C. minutus Lindberg, 1953; C. canariensis Wollaston, 1858; C. hayeki (Cobos, ); C. obtusus Wollaston, 1864: 213; C. palmensis (Cobos, ); C. mateui (Cobos, ); C. obscurus Wollaston, 1864. The following species differed in that the distal sclerites did not have a petiole‐like base: C. globulicollis Wollaston, 1862; C. brunneipennis Wollaston, 1863; C. mendizabili (Cobos, ); C. arozarenai (Cobos, ), distal sclerites absent; C. fernandezi (Cobos, ); C. gomerensis (Cobos, ).…”
Section: Taxonomymentioning
confidence: 99%
See 3 more Smart Citations
“…All available illustrations of Coptostethus species were examined (Cobos , , ; Németh & Platia ; Platia , ; Platia & Kakiopoulos ) to identify variability in diagnostic characters in the bursa copulatrix sclerites. The following species had proximal sclerites moderate to broad (Figs 21,24), nearly symmetrical with a median groove and narrow (petiolate) base; distal sclerites fused and weakly sclerotized, and base of spermathecal gland duct surrounded by sclerotized ring: Coptostethus buci Németh & Platia, ; C. salvatoi Platia in Platia & Kakiopoulos, ; C. oromii (Cobos, ); C. machadoi (Cobos, ); C. vittatus (Lindberg, 1953); C. crassiusculus Wollaston, 1864; C. vestitus Lindberg, 1953; C. minutus Lindberg, 1953; C. canariensis Wollaston, 1858; C. hayeki (Cobos, ); C. obtusus Wollaston, 1864: 213; C. palmensis (Cobos, ); C. mateui (Cobos, ); C. obscurus Wollaston, 1864. The following species differed in that the distal sclerites did not have a petiole‐like base: C. globulicollis Wollaston, 1862; C. brunneipennis Wollaston, 1863; C. mendizabili (Cobos, ); C. arozarenai (Cobos, ), distal sclerites absent; C. fernandezi (Cobos, ); C. gomerensis (Cobos, ).…”
Section: Taxonomymentioning
confidence: 99%
“…nov.* (from Cardiophorus alepensis Pic, : 10); Coptostethus arozarenai (Cobos, 1969) comb. nov. ; C. attilai Németh & Platia, ; Coptostethus auarita (Liberto and Wurst, 1999) comb. nov. ; C. bonitaensis Platia, 2015; Coptostethus brancuccii (Platia & Schimmel, ) comb.…”
Section: Taxonomymentioning
confidence: 99%
See 2 more Smart Citations
“…Th e specimens preserved in alcohol were received by the authors, and during the process of identifi cation, we found one species, Cardiophorus rufi collis (Linnaeus, 1758), as new to Morocco and North Africa, and one belonging to the genus Elathous Reitter, 1890 as new for science. According to the Palaearctic catalogue (Cate 2007) and subsequent contributions (Platia 2008a, b, 2011, 2013, 2014, Németh & Platia 2014) about 80 species of Elateridae are known from Morocco -the subfamily Cebrioninae with 39 species (Cate 2007) is not included.…”
Section: Introductionmentioning
confidence: 99%